Lectotypification of Dracocephalum royleanum (Lamiaceae) - Turdiboev, Obidjon A.; Mamatqosimov, Odilbek T.; Celep, Ferhat (Phytotaxa, 2021)
During our literature and herbarium studies, we have come across a typological issue regarding the name Dracocephalum royleanum (= Lallemantia royleana). In this paper, the nomenclatural history of L. royleana is presented and typification of D. royleanum is proposed.